The effect of rifampicin and pyrazinamide on isoniazid pharmacokinetics in rats - Baldan, Helen M. [UNESP]; De Rosa, Helene J. [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Ximenes, Valdecir Farias [UNESP]; Machado, Rosangela G. P. [UNESP] (Wiley-Blackwell, 2007)
Tuberculosis chemotherapy involves combination of the drugs isoniazid (INH), rifampicin (RMP) and pyrazinamide (PYR) for a 6-month period. The present work investigated the influence of RMP and PYR on the pharmacokinetic parameters of INH when groups of rats were pre-treated for 21 days with INH alone or in combination with RMP and/or PYR, in the following amounts per kg body weight: INH 100 mg; INH 100 mg + RMP 100 mg; INH 100 mg + PYR 350 mg; INH 100 mg + PYR 350 mg + RMP 100 mg. It was found that the co-administration of PYR caused an increase in the INH distribution volume (V-d/F), half-life of elimination t(1)/2(beta)) and clearance (Cl-T/F), and a decrease in the area under curve 0 to 24 h (AUC). Co-administration of RMP caused an increase in the Cl-T/F and a decrease in the AUC. The combination INH + PYR + RMP caused an increase in the Cl-T/F and a decrease in the AUC. These significant pharmacokinetic interactions between the tuberculostatic drugs might be related to differences in the therapeutic and toxic effects. Copyright 0( 2007 John Wiley & Sons, Ltd.
Keywords: pharmacokinetics; isoniazid; pyrazinamide; rifampicin